Predictive risk factors of treatment-refractory complex lung disease: a single-center retrospective cohort study - Takahiko Saito; Yuya Aono; Masato Kono; Masaki Ishige; Takuma Sugiura; Misato Higasa; Fumiya Nihashi; Mineo Katsumata; Hideki Miwa; Yoshihiro Miki; Dai Hashimoto (Therapeutic Advances in Infectious Disease)
Background: Mycobacterium avium complex lung disease (MAC-LD) is a chronic, progressive, potentially life-threatening infection. Some cases are refractory to standard guideline-based therapy (GBT), and sputum cultures are persistently positive for acid-fast bacilli. Although an early identification of treatment-refractory MAC-LD is crucial, its risk factors remain unknown. Objectives: We aimed to identify the risk factors for refractory MAC-LD in response to initial GBT. Design: A retrospective single-center study was conducted involving consecutive patients with MAC-LD who were diagnosed between 2006 and 2024 and received initial GBT. Methods: Refractory MAC-LD was defined as sputum culture positivity at least 6 months after the initial GBT. Prognostic factors were identified using Cox proportional hazards analysis, and risk factors for refractory MAC-LD were examined using logistic regression analysis. Results: Of the 201 patients with definite MAC-LD, 35 (17.4%) had refractory MAC-LD. Patients with refractory MAC-LD had a significantly lower body mass index (BMI), more cavitary lesions on high-resolution computed tomography (HRCT), and higher mortality (log-rank test, p  = 0.006) compared to those with non-refractory MAC-LD. A multivariate analysis adjusted for age and sex showed that refractory MAC-LD (adjusted hazard ratio (HR): 2.76; 95% confidence interval (CI): 1.10–6.95; p  = 0.030) and cavitary lesions on HRCT (adjusted HR: 2.77; 95% CI: 1.34–5.70; p  = 0.005) were significantly associated with all-cause mortality. In addition, a multivariate analysis revealed that lower BMI (odds ratio (OR): 0.68; 95% CI: 0.55–0.85; p  < 0.001) and cavitary lesions on HRCT (OR: 2.52; 95% CI: 1.15–5.50; p  = 0.020) were independent risk factors of refractory MAC-LD. Conclusion: Low BMI and cavitary lesions on HRCT are risk factors for refractory MAC-LD.